The Structure-Phase Compositions of Ni - Cr and Co–Cr Based Powder Alloys Coatings Deposited by Plasma-Detonation on Steel Substrates - Alontseva, Darya L.; Pogrebnjak, Alexander D.; Klassen, Galina (International Conference on Plasma Surface Engineering, 2013)
This paper presents new results of transmission electron microscopy (TEM), X-ray diffraction (XRD) and atomic force microscopy (AFM) investigation of the structure-phase compositions of thick (150 µm) coatings on the base of Ni–Cr and Co–Cr deposited by plasma-detonation on steel substrates. The phase structures and morphology of precipitation from solid solution are defined. The microstructure model of a thick plasma detonation coating on steel substrate is developed. The main aim of carrying out these investigations is developing science based recommendations for modification of plasma-detonation coatings by plasma-jet or e-beam.